Synthesis and Spectral Studies of Substituted Phenyl and Naphthyl imino-1,2,3,4-tetrahydrocarbazoles - VELMURUGAN, R.; SEKAR, M. (Asian Journal of Chemistry, 2010)
The reaction of 1-oxo-1,2,3,4-tetrahydrocarbazole (1) and aniline (2a-c) in ethanol and refluxed for 1 h at 120 °C afforded phenyl imino- 1,2,3,4-tetrahydrocarbazole derivatives (3a-c). The same reaction of 1-oxo-1,2,3,4-tetrahydrcarbazole and naphthylamine (4) in ethanol and refluxed for 1 h at 120 °C yielded naphthyl imino-1,2,3,4-tetrahydrocarbazole (5).